Personal protective equipment - MARCOM Group, Ltd. (Wilmington, Del.).; Training Network; Long Island Productions (Durham, NC Training Network, 2004)
Covers all body areas that need protection. Motivates workers to match protective equipment to the hazard. Offers guidelines for the proper use and maintenance of personal protective equipment.
DVD.
Keywords: Industrial safety; Protective clothing